2010
DOI: 10.3989/gya.087009
|View full text |Cite
|
Sign up to set email alerts
|

Variations in fatty acid composition, glucosinolate profile and some phytochemical contents in selected oil seed rape (<i>Brassica napus</i> L.) cultivars

Abstract: Rapeseed (Brassica napus L.) is now the third most important source of edible oil in the world after soybean and palm oil. In this study seeds of five different rapeseed cultivars namely; pactol, silvo, topas, serw 4 and serw 6 were evaluated for their fatty acid composition, glucosinolate profile, amino acids, total tocopherols and phenolic content. Among all cultivars significant variability in fatty acids were observed. The oleic acid (C18:1) ranged from 56.31% to 58.67%, linoleic acid (C18:2) from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…[27,28] Methionine-derived glucosinolates are found in Brassica species. [29] The Brassica samples contained 8 aliphatic, 3 indolyl, and 2 aromatic glucosinolates, which was agreed with Elbeltagi's study [19] ; though, the total glucosinolate content was lower (4.40 to 5.90 µmol/g) in their study. The contents and odor intensities of degradation products generally depend upon the precursors.…”
Section: Change Of Glucosinolates As Volatile Flavor Precusorsupporting
confidence: 83%
See 1 more Smart Citation
“…[27,28] Methionine-derived glucosinolates are found in Brassica species. [29] The Brassica samples contained 8 aliphatic, 3 indolyl, and 2 aromatic glucosinolates, which was agreed with Elbeltagi's study [19] ; though, the total glucosinolate content was lower (4.40 to 5.90 µmol/g) in their study. The contents and odor intensities of degradation products generally depend upon the precursors.…”
Section: Change Of Glucosinolates As Volatile Flavor Precusorsupporting
confidence: 83%
“…[16][17][18] Some of the previous studies have reported the relationship between glucosinolate degradation and the pungent odor in cold pressed rapeseed oil. [14,19] The sulfur compounds from rapeseed oils possess low threshold and strong odor. Very few studies have reported the distribution of glucosinolates, volatile isothiocyanates and sulfur compounds, and pungent odor difference in different genetic types of rapeseed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the patterns of abundance of fatty acid in the seeds were inconsistent with rapeseed oil reported by (12). In this reference, oleic acid was the most abundant one consisting of 56.31% to 58.67% followed by linoleic acid of ranges 10.52% to 13.74% as compared to 51.38% in the prekesse seed.…”
Section: Discussioncontrasting
confidence: 71%
“…Similarly, El-Beltagi and Mohamed [63] investigated the variation in fatty acid composition of oilseed rape and found that oleic acid (C18:1) ranged from 56.3% to 58.7%, linoleic acid (C18:2) from 10.5% to 13.7%, α -linolenic acid (C18:3) from 8.8% to 10.3%, and erucic acid (22 : 1) from 0.15% to 0.91%. Xun et al [64] investigated the long-term effect of human diets containing omega-3 polyunsaturated fatty acids on the occurrence of hypertension, revealing that the individuals with the highest intake of these compounds had a significantly lower incidence of hypertension.…”
Section: Discussionmentioning
confidence: 99%